Development and initial validation of the sport education scale - Burgueño, Rafael; Calderón, Antonio; Sinelnikov, Oleg; Medina-Casaubón, Jesús (Taylor & Francis, 2022)
This research developed and psychometrically tested the Sport Education Scale, a measure of students’ perceptions of the structural features of a Sport Education season. In the first study (N = 277 students), a pool of 28 items was developed, and an exploratory factor analysis found a 7-factor solution. In the second study (N = 656 students), a confirmatory factor analysis verified the 28-item 7-factor correlated model, which was invariant across gender and age. Convergent validity was met by suitable average variance extracted values. Discriminant validity was underpinned by appropriate values for heterotrait-monotrait ratio of correlations and correlations among latent factors. Reliability was adequate for each factor of the Sport Education Scale. A structural equation modeling showed that Sport Education positively predicted perceived competence, sportsperson- ship, and intrinsic motivation among students. The Sport Education Scale is a valid and reliable instrument to assess the core elements of this pedagogical model
https://openpolicyfinder.jisc.ac.uk/id/publication/5844?from=single_hit
Keywords: Educación física - Estudio y enseñanza; Investigación activa en educación; Physical education; Model-based practice; Teaching and learning model; Psychometric analysis